A Proposal Concerning Assessment of Alternative Cityscape Designs with Audiovisual Comfort and Health of Inhabitants - OZGA, Agnieszka; WIERZBICKI, Jacek; MLECZKO, Dominik (Archives of Acoustics, 2023)
The research concerning the future of sound in towns and cities is focused on two main issues: studies are conducted separately on the comfort, i.e., assessment of visual scenery and sound levels in a cityscape and separately, on the health protection issues. The policy of the acoustic environment control with regard to the health of its inhabitants is traditionally connected with measurements of noise levels presented with the help of the coefficients Lden and Lnight noise indicators, while the models based on tranquillity rating (TR) with the help of the coefficients LAmax, LAmin, LAeq, LA10. None of these coefficients refers to the soundscape. In this paper, we present a justification of the necessity to enter into discussion on the need to combine these research areas. The authorities managing towns and cities of the future should be provided with tools enabling them to assess modernisation projects from the point of view of both health and comfort of inhabitants. We present our ideas treating them as an invitation to a scientific discourse, in the form of analysis of actual projects concerning modification of existing cityscapes. The modifications are aimed at returning some unfavourably developed spaces to the inhabitants. When analysing the changes proposed in the projects, we take into account two models of the revitalised area quality assessment. The first model is used to assess the effect of noise on health. The second model, based on the indicator known as the TR, serves simultaneous assessment of an area from both visual and acoustical aspects. The models used contemporarily by scientists show multiple flaws, therefore, for the TR indicator we propose a modification taking the sound structure into account. The modification embodies the idea of masking unpleasant sounds with friendly ones. The changes to the model are presented, in this paper, in the context of two projects which were worked out in the framework of 12th edition of the intercollegiate workshop cycle The New Cityscapes. In the course of each workshop of the cycle, we combined art, science, and technology in order to seek solutions creating a better future. In view of the importance of this issue and the need to introduce a certain level of universalism, the authors offer an invitation to join a discussion on the future of sound in urban agglomerations.